Nodular expression of seminoma in the neck: An unusual case presentation - Charles K. Crawford, BS; Mohammad Yasrab, MD; Elliot K. Fishman, MD (Radiology Case Reports)
Seminoma is a malignant germ cell tumor that primarily develops in the testis but can occur in other extragonadal areas, most commonly the mediastinum and retroperitoneum. While generally offering a favorable prognosis, seminomas can sometimes clinically present with misleading characteristics resulting in delayed diagnosis. In this article, we report the case of a 31-year-old male diagnosed with grade IIIC intermediate risk testicular seminoma cTxN3M1bSx, who presented initially with a palpable cervical mass. We focus on the use of radiological modalities for an optimized diagnosis by coordinating our imaging with pathological findings and clinical presentation.